Antibacterial activity of mycelial extract from a local fungus, Sclerotium rolfsii - Zahra, Muhandinni; Aryantha, I Nyoman Pugeg; Sukrasno, Sukrasno; Suhardi, Veronica Sri Harjati (Universitas Gadjah Mada, 2025)
Mycelium‐to‐sclerotium differentiation in fungi involves not only morphological but also biochemical changes throughout the process, which may contribute to their persistence and be a possible source of bioactive compounds. This study aims to evaluate the antibacterial activity and identify the bioactive compound in the local isolate Sclerotium rolfsii. Fungal culture was grown in media containing potato extract (20 g/L), dextrose (20 g/L), and peptone (5 g/L) for 27 days under static conditions at room temperature. Mycelium, sclerotium and filtrate were collected every three days and extracted with methanol, followed by evaporation and antibacterial screening. Significant activity was observed in day three of mycelial extract, which showed morphology of initial sclerotium formation (MIC 0.39 mg/mL) against B. subtilis and E. coli. An improved extraction method (sequential extraction) was employed for mycelial sample on the third day. N‐hexane and ethyl acetate extracts exhibited stronger activities (0.20 mg/mL). Ergosterol was identified after TLC‐bioautography, radial chromatography, and NMR elucidation analysis. S. rolfsii mycelium (third day‐sclerotial initiation) was found to contain ergosterol, demonstrating strong defense against bacteria, and possibly related to sclerotium‐differentiation metabolites. These findings may pave the way for more extensive studies of sclerotium differentiation as an interesting phenomenon of fungal development and bioactive compound origins.